The effects of school‐based interventions on physiological stress in adolescents: A meta‐analysis. (26th July 2021) - van Loon, Amanda W. G.; Creemers, Hanneke E.; Okorn, Ana; Vogelaar, Simone; Miers, Anne C.; Saab, Nadira; Westenberg, P. Michiel; Asscher, Jessica J.
Abstract: Chronic stress is associated with dysregulations in the physiological stress system, resulting in diverse negative developmental outcomes. Since adolescence is a period characterized by increased stress‐sensitivity, and schools are an important environment for the developing adolescent, school‐based interventions promoting psychosocial functioning are of particular interest to prevent adverse outcomes. The present study therefore aimed to investigate the effectiveness of such interventions on hypothalamic pituitary adrenal‐axis (i.e., cortisol) and cardiovascular (i.e., blood pressure [BP] and heart rate [HR]/heart rate variability [HRV]) parameters of stress in adolescents, and examined moderators of effectiveness. The search resulted in the inclusion of k = 9 studies for cortisol, k = 16 studies for BP, and k = 20 studies for HR/HRV. The results indicated a significant small overall effect on reducing BP, but no significant effect for HR/HRV. For cortisol, large methodological variation in the few primary studies did not allow for quantitative analyses, but a qualitative review demonstrated inconsistent results. For BP and HR/HRV, larger effects were observed for intervention programs with a mindfulness and/or meditation component, for interventions without a cognitive‐behavioural component and for interventions with a higher intensity. Providing adolescents with techniques to improve indicators of physiological stress may prevent emerging mental health problems.